Nourishing student success and wellbeing - Teresa Warne; Roland Ebel; Selena Ahmed (Journal of Agriculture, Food Systems, and Community Development, 2023)
Food insecurity among U.S. college and university students surpasses respective levels in the general population. Previous research has primarily focused on demographic and economic explanations, neglecting other risk factors such as student place of residence and specific food environments. In addition, most studies have been conducted before the COVID-19 pandemic, which further exacerbated food security challenges. To address these gaps, our comprehensive case study at Montana State University (MSU) assessed risk factors for student food insecurity, considering food access and the students’ food environments. From March to November 2020, we collected online survey responses from a diverse sample of 443 MSU students. Approximately one–third experienced food insecurity during this period, with their food insecurity status linked to housing type and academic level. Despite students' reported knowledge of healthy diets and cooking skills, consuming inadequate and insufficient food had a significant impact on their dietary quality, well-being, and physical and mental health. Just under half of the surveyed students (44%) reported increased difficulties in accessing food due to the pandemic. Addressing food insecurity among college students is crucial for their well-being and academic success, not only because of additional stressors such as COVID-19. Dealing with food insecurity requires improving economic situations and creating a reliable and diverse food environment that ensures affordable, healthy, safe, convenient, desirable, and sustainable food options. Special increased support from universities and governments should be given to students living off-campus. By recognizing these unique challenges and implementing targeted interventions, we can foster a supportive food environment for students.